Lipid sources in diets for egg-laying japanese quail: performance and egg quality - Bertipaglia, Letícia Abaker (2016)
This study evaluated the effect of using lipid sources of plant and animal origin in diets for Japanese quail (Coturnix coturnix japonica) on production performance and internal egg quality. Japanese quails (n = 160) were distributed in a completely randomized design with four treatments and eight replications of five birds each. Lipid sources evaluated were: soybean oil, from poultry slaughterhouse, fish waste and grape seed. The characteristics of performance and internal egg quality were measured every 21 days for a total period of 84 days. Data were subjected to analysis of variance and the means were compared by Tukey’s test. There was no effect of treatments on the production performance of birds, except for feed intake, which was higher for birds fed grape seed oil in the diet. Lipid sources evaluated had no influence on the internal egg quality. It can be concluded that the lipid sources evaluated here in can be used as alternative energy in feed for laying quails, without affecting the performance and internal egg quality.